The Effectiveness of Digital Platforms in Enhancing Students’ English Vocabulary Mastery in SMA AL Quran Wahdah Islamiyah Kendari - Iwan; Sam Hermansyah; Titin Rahmiatin Rahim; Yuliyanah Sain (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
Vocabulary mastery is fundamental to English language proficiency, yet many Indonesian senior high school students continue to face challenges in acquiring adequate vocabulary due to conventional teaching methods. This study aimed to investigate the effectiveness of digital platforms in enhancing English vocabulary mastery among eleventh-grade students at SMA Al Quran Wahdah Islamiyah Kendari. A pre-experimental one-group pretest-posttest design was employed, involving 23 students from Class XI selected through purposive sampling. The intervention consisted of systematic vocabulary learning activities utilizing selected digital platforms over an eight-week period. Data were collected through a validated vocabulary achievement test administered before and after the treatment. Quantitative data were analyzed using descriptive statistics and paired-sample t-test. The findings revealed a statistically significant improvement in students’ vocabulary scores following the implementation of digital platforms (p < 0.05). Students also reported higher motivation and engagement during the learning process. This study concludes that digital platforms constitute an effective, accessible, and student-centered tool for improving vocabulary acquisition in EFL contexts. The results offer practical implications for English teachers and curriculum developers seeking to integrate technology in technology-limited or faith-based secondary schools in Indonesia.